Quasi-random numbers in some statistical systems - Rudzkienė, Vitalija (Lietuvos matematikos rinkinys, 2000)
There are many ways to get random numbers. Some methods include making hardware devices that generate noise, observing cosmic ray flux and etc. Pseudo-random numbers come from mathematical functions and algorithms that provides such numbers called pseudo-random generators. The generators chosen is often that provided by the software developer. The most popular way for getting pseudo-random numbers is by statistical programming systems. In Lithuania these statistical systems are in use: Statistica, Statgraphics, SAS, SPSS. Statistical properties of random sequences, generated by these statistical systems, are investigated in this paper.